Simplify: 7y^2 -2y+7-(-2y^2+1/2y-3)(2y)

1 answer

To simplify this expression, we first need to distribute the 2y to all terms inside the parentheses:

7y^2 - 2y + 7 - (-2y^2 + 1/2y - 3)(2y)
= 7y^2 - 2y + 7 + 4y^3 - y + 6

Next, we combine like terms:

7y^2 + 4y^3 - 2y - y + 7 + 6
= 4y^3 + 7y^2 - 3y + 13

Therefore, the simplified expression is 4y^3 + 7y^2 - 3y + 13.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions